2023
DOI: 10.1038/s41467-023-36505-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical functions of SNAIL drive context-specific cancer progression

Abstract: SNAIL is a key transcriptional regulator in embryonic development and cancer. Its effects in physiology and disease are believed to be linked to its role as a master regulator of epithelial-to-mesenchymal transition (EMT). Here, we report EMT-independent oncogenic SNAIL functions in cancer. Using genetic models, we systematically interrogated SNAIL effects in various oncogenic backgrounds and tissue types. SNAIL-related phenotypes displayed remarkable tissue- and genetic context-dependencies, ranging from prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Many in vitro as well as computational studies have reported SNAIL as a key transcriptional regulator driving EMT and metastasis formation. However, a recent in vivo study on mouse model of pancreatic ductal adenocarcinomas (PDAC) provided a counter perspective by showing that SNAIL deletion does not block EMT and is thus not rate-limiting for EMT and metastasis 51 . Also, different member of SNAIL family of transcription factors have diverse functionality and not all of them induce EMT.…”
Section: Resultsmentioning
confidence: 99%
“…Many in vitro as well as computational studies have reported SNAIL as a key transcriptional regulator driving EMT and metastasis formation. However, a recent in vivo study on mouse model of pancreatic ductal adenocarcinomas (PDAC) provided a counter perspective by showing that SNAIL deletion does not block EMT and is thus not rate-limiting for EMT and metastasis 51 . Also, different member of SNAIL family of transcription factors have diverse functionality and not all of them induce EMT.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in (Figure 7A), besides SNAI1 , no other genes exhibited robust upregulation upon acetyl-CoA supplementation in ACSL4 knockdown cells compared to control. Since SNAIL has been extensively and conclusively characterized as a master regulator of EMT process, initiating cancer cell plasticity, migration, and metastatic dissemination across diverse tumor types 32, 51, 52 . The downregulation of SNAIL in ACSL4 knockdown cells highlights its role in impeding the metastatic potential of TNBC, emphasizing the significance of lower SNAIL expression following ACSL4 activity loss.…”
Section: Resultsmentioning
confidence: 99%
“…In PDAC, mouse models revealed that EMT occurs extremely early in disease progression in disseminating tumor cells, even before the development of a primary tumor [ 12 ]. In contrast, intriguing recent studies have suggested that metastasis can occur in the absence of EMT [ 24 , 25 , 28 ], and that canonical EMT factors may promote tumor progression by EMT-independent pathways [ 29 ]. For example, Zheng reported that EMT is not required for invasion or metastasis in PDAC [ 30 ].…”
Section: Epithelial-to-mesenchymal Transition In Pdacmentioning
confidence: 99%